2016
DOI: 10.1111/dme.13107
|View full text |Cite
|
Sign up to set email alerts
|

Sodium‐glucose co‐transporter‐2 inhibitors suppress atrial natriuretic peptide secretion in patients with newly diagnosed Type 2 diabetes

Abstract: This study shows the ability of sodium-glucose co-transporter-2 inhibitors to lower atrial natriuretic peptide levels and improve glycaemic control, which may benefit the cardiovascular system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 14 publications
(15 reference statements)
2
17
0
Order By: Relevance
“…A total of 28 newly diagnosed T2DM patients met inclusion criteria (18 in dapagliflozin group and 10 in placebo group) and were admitted to the study. As we reported, the demographic and baseline characteristics of study subjects were similar between placebo and dapagliflozin groups [ 13 ].…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…A total of 28 newly diagnosed T2DM patients met inclusion criteria (18 in dapagliflozin group and 10 in placebo group) and were admitted to the study. As we reported, the demographic and baseline characteristics of study subjects were similar between placebo and dapagliflozin groups [ 13 ].…”
Section: Resultsmentioning
confidence: 84%
“…Dapagliflozin reduced hyperglycemia, body weight, and SBP and effectively addressed three CVD risk factors in older patients with poorly controlled T2DM and CVD [ 6 , 11 ]. However, we observed that dapagliflozin may benefit the cardiovascular system through the reduced atrial natriuretic peptide levels [ 13 ]. The smoothed blood glycemic executions might confer another protection mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dose-related 24-hour urine volume and hematocrit increased minimally [ 20 ]. More recently, newly diagnosed patients with T2DM treated with SGLT2is had reduced atrial natriuretic peptide levels, which may benefit the CV system [ 23 ].…”
Section: Reviewmentioning
confidence: 99%